MEMBANGUN KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA - Wahid Umar (IKIP Siliwangi and I-MES, 2012)
Until now, the role of teachers in building students' mathematical communication skills, especially in mathematics is still very limited. Communication skills are a very important aspect that needs to be owned by students who want to succeed in their studies. Similarly, according to Kist (Clark, 2005) effective communication skills is an ability that needs to be owned by the students for all subjects.Â Mathematical communication skills (mathematical communication) in the learning of mathematics is very necessary to be developed. This is because through mathematical communication students can organize mathematical thinking both orally and in writing. In addition, students are also able to provide an appropriate response among students and media in the learning process. Even in the association community, someone who has good communication skills will tend to be more adaptable to anyone where it is located in a community, which in turn will be a success in life.In this paper, the author presents the notion of mathematical communication skills, with coverage of two things: the ability of students to use mathematics as a tool of communication (language of mathematics), and the student's ability to communicate mathematics is learned as the content of the message should be delivered. How and why communication is important to build a mathematical community through open communication in the classroom.Â